PENGARUH SIKAP KREATIF TERHADAP PEMAHAMAN MEMBACA TEKS BAHASA INGGRIS - Maharani Putri (STKIP Pesisir Selatan, 2018)
ABSTRACTThis research was aimed to find out the influence of students creative attitude and learning style toward their reading comprehension for second year of SMK YPM Zain Pauh Kambar Padang Pariaman in 2013/2014 academic year. This research was quantitative approach. The sample of this research was 62 students who were taken by using random sampling technique. The data were collected by using questionnaire and reading comprehension test. Qualitative data was analyzed by using simple and multiple regression technique with SPSS version 16.0 for windows. The research findings show that creative attitude gave influence toward students reading comprehension. In addition, students who have high creative attitude were also have high score in reading comprehension than students who have fair and low creative attitude.Key Words: Students Creative Attitude, Reading Comprehension